Clinical and functional outcomes of patients undergoing anterolateral versus anteromedial surgical approaches for pilon fractures. Issue 1 (January 2019) - Crist, Brett D.; Worley, John R.; Jenkins, Tyler J.; Khazzam, Michael S.; Della Rocca, Gregory J.
Abstract : Background: This study examined the clinical and functional outcomes for two of the most common surgical approaches for pilon fractures: the anteromedial (AM) and anterolateral (AL) approaches to the distal tibia. Methods: A retrospective chart review was performed for 75 patients who underwent operative management of pilon fractures between September 2005 and July 2009. Clinical data points included patient demographics, comorbidities, fracture classification, complications, and days from surgery to clinical and radiographic fracture union. Outcome scores were obtained via phone interview at a single cross-section time point. Results: The AL group had a significantly higher average AO/OTA fracture classification than the AM group (AO/OTA 43 C3 vs. C1) in both the retrospective chart review and the phone interview subanalysis. Despite this difference, the AL group had significantly fewer amputations and shorter time to radiographic healing ( P <0.05). In the phone interview subanalysis, functional outcome scores were not significantly different ( P >0.05). Average time from surgery to survey collection was 3.28 yr for the AL group and 3.54 yr for the AM group. Conclusions: The approach to pilon fractures should be dictated by the specific fracture pattern and associated soft-tissue injury. Our study shows that both AL and AM approaches had equivalent functional outcomes. This study highlights the importance of choosing the correct surgical approach when operating on pilon fractures and that the AL approach can successfully be used to treat the most complex fractures with fewer soft-tissue complications and faster radiographic healing versus the AM approach.